Structural response recovery based on improved multi-scale principal component analysis considering sensor performance degradation - Ma, S.; Li, Jun; Hao, Hong; Jiang, S. (Multi-Science Publishing, 2018)
This article proposes an improved multi-scale principal component analysis approach to recover the structural dynamic response in the time domain from data measured by performance-deteriorated sensors. The proposed approach builds on discrete wavelet transform, principal component analysis, and inverse discrete wavelet transform. The main approach is based on a cross-correlation calculation to better preserve the true structural vibration behavior as well as to recover the structural response from data measured by deteriorated sensors. Three sensor performance degradation models are considered in this study. Numerical studies are conducted first to demonstrate the effectiveness and accuracy of the proposed approach to recover the structural vibration response of an example spatial truss model considering sensor performance degradation under different loading scenarios. Experimental data on an in-field benchmark bridge are also analyzed to further validate and demonstrate the performance of the proposed approach.